Litchi and longan : botany, production and uses - Menzel, C. M. (Christopher M.); Waite, G. K. (Geoff K.) (CAB books., 2005)
Litchi (lychee) and the related fruit longan are grown extensively in China and South-East Asia, as well as in Australia, Florida (USA), Southern Europe and Southern Africa. This book represents a comprehensive, balanced and internationally focused publication on these fruit.